The Concept of Mubadalah as the Basis for the Protection of Human Rights in Islamic Family Law - Sholikin, Nur; Rahmad Setyawan; Muhammad Asyrofudin; Khairuddin; Samsudin, Muhammad Adib (UIN Sunan Kalijaga Yogyakarta, 2025)
Islamic family law regulations in Indonesia are still influenced by traditional understandings that tend to be textual-normative, especially in issues of child marriage, polygamy, financial responsibility, child custody, and inheritance distribution. This condition poses challenges in realizing gender justice and the protection of human rights. This study aims to analyze the concept of mubadalah as a humanistic and equitable approach to interpretation, as well as its potential as a basis for the protection of human rights in Islamic family law. This study is a literature study with a normative juridical approach. Data was obtained through a review of legislation, the Compilation of Islamic Law (KHI), the Qur’an, hadith, classical books, journal articles, and other relevant literature. The analysis was conducted descriptively and qualitatively by interpreting religious texts contextually. The results of the study show that the concept of mubadalah emphasizes reciprocity, justice, and shared responsibility between men and women. In the context of Islamic family law, this approach emphasizes the protection of children in child marriages, makes justice the benchmark in polygamy, interprets alimony as a shared responsibility, emphasizes joint custody and the best interests of the child, and opens up room for ijtihad in the distribution of inheritance. Thus, the concept of mubadalah can be used as a conceptual basis for reforming Islamic family law to bring it into line with the principles of gender justice and human rights protection. Regulasi Hukum keluarga Islam di Indonesia masih dipengaruhi oleh pemahaman tradisional yang cenderung tekstual-normatif, terutama dalam isu perkawinan anak, poligami, tanggung jawab nafkah, hak asuh anak, dan pembagian harta warisan. Kondisi ini menimbulkan tantangan dalam mewujudkan keadilan gender dan perlindungan hak asasi manusia (HAM). Penelitian ini bertujuan menganalisis konsep mubadalah sebagai pendekatan tafsir yang humanis dan berkeadilan, serta potensinya sebagai landasan perlindungan HAM dalam hukum keluarga Islam. Penelitian ini merupakan penelitian kepustakaan dengan pendekatan yuridis normatif. Data diperoleh melalui kajian terhadap peraturan perundang-undangan, Kompilasi Hukum Islam (KHI), al-Qur’an, hadis, kitab klasik, artikel jurnal, dan literatur relevan lainnya. Analisis dilakukan secara deskriptif-kualitatif dengan menafsirkan teks-teks keagamaan secara kontekstual. Hasil penelitian menunjukkan bahwa konsep mubadalah menekankan adanya kesalingan, keadilan, dan tanggung jawab bersama antara laki-laki dan perempuan. Dalam konteks hukum keluarga Islam, pendekatan ini menegaskan pada perlindungan anak dalam perkawinan anak, menjadikan keadilan sebagai tolak ukur dalam poligami, memaknai nafkah sebagai tanggung jawab bersama, menitikberatkan hak asuh secara bersamaan dan kepentingan terbaik untuk anak, serta membuka ruang ijtihad dalam pembagian warisan. Dengan demikian, konsep mubadalah dapat dijadikan landasan konseptual dalam pembaruan hukum keluarga Islam agar selaras dengan prinsip keadilan gender dan perlindungan HAM.